Analysis of Construction Dispute Resolution Reform Perspective of Law Number 2 of 2017 - Waisapi, Jeffry Yuliyanto (Journal of Law, Politic and Humanities, 2024)
Indonesia is pursuing development to enhance welfare through projects like office buildings, housing, and infrastructure. The involvement of societal levels is crucial for success. However, development can trigger disputes from differing interpretations or contractual provisions. This study focuses on analyzing reforms in construction dispute resolution under Law No. 2 of 2017, utilizing a quantitative survey approach. The Construction Services Acts of 1999 and 2017 marked significant shifts in philosophical outlook and dispute resolution mechanisms. Findings indicate that the 2017 Act emphasizes non-litigious settlements with a "win-win" approach, though challenges remain regarding the term "court." Despite these challenges, the study acknowledges that Indonesia is progressing towards effective construction dispute resolution. It recommends stricter sanctions for violations of construction agreements to enhance future regulatory frameworks. These insights are vital for legal practitioners and policymakers, aiming to refine mechanisms and raise public awareness on regulatory gaps that hinder sustainable development in Indonesia. The study also categorizes dispute resolution solutions and scrutinizes provisions in Law No. 2 of 2017 concerning defects, nonconformities, weaknesses, and perceived biases. The Act defines a team formed by mutual agreement to oversee Construction Services, tasked with preventing and mediating disputes arising from Construction Work Contracts